Spark plug electrode and spark plug

JP2025032702AActive Publication Date: 2025-03-12DENSO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023138133
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-03-12
Estimated Expiration
2043-08-28

AI Technical Summary

Benefits of technology

【0009】 上記スパークプラグ電極は、上記構成を有している。また、上記スパークプラグは、上記スパークプラグ電極を有している。そのため、上記スパークプラグ電極および上記スパークプラグによれば、溶融再凝固部と貴金属合金チップとの第1の境界側、および、溶融再凝固部とNi合金母材との第2の境界側の両方において貴金属比率の範囲を従来よりも広げても、冷熱サイクルによるクラック進展を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032702000001_ABST
    Figure 2025032702000001_ABST
Patent Text Reader

Abstract

To provide a spark plug electrode that can secure connection reliability of a Ni alloy base material and a nobel metal chip alloy in a state where a range of a noble metal ratio is more expanded than conventional one on both boundary sides of a fusing re-solidification part, a nobel metal chip, and the Ni alloy base material, and provide a spark plug.SOLUTION: A spark plug electrode 1 includes a fusing re-solidification part 103 between a Ni alloy base material 101 and a nobel metal chip 102, the fusing re-solidification part containing both components. The nobel metal chip 102 is formed by an Ir-Pt-Ta alloy containing 2 to 23 mass% of Pt, and 0.3 to 5.4 mass% of Ta. The fusing re-solidification part 103 satisfies βmax≤3.6, 25%≤α1ave, and α2ave≤90%, where the following equation is satisfied: βmax=α2max / α1min, the minimum value of a noble metal ratio α1 on a first virtual line L1 of α1min, the maximum value of a noble metal ratio α2 on a second virtual line L2 of α2max, an average value of the noble metal ratio α1 of α1ave, and an average value of the noble metal ratio α2 of α2ave.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spark plug electrode and a spark plug. [Background technology]

[0002] 2. Description of the Related Art As described in Patent Document 1, a spark plug electrode is known that includes a center electrode having an electrode base material and a precious metal alloy tip made of an Ir-Rh alloy welded to the electrode base material.

[0003] According to Patent Document 1, by adopting a configuration in which a mixture portion formed between the electrode base material and the precious metal alloy chip, in which the components of the electrode base material and the components of the precious metal chip are mixed, in which the precious metal ratio in a first specified region adjacent to the boundary with the precious metal alloy chip is 40% by weight or more, and in which the precious metal ratio in a second specified region adjacent to the boundary with the electrode base material is 80% by weight or less, it is possible to stably ensure the reliability of the joint between the electrode base material and the precious metal tip alloy. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-82539 Summary of the Invention [Problem to be solved by the invention]

[0005] The technology of Patent Document 1 has room for improvement in the following respects. That is, as described in the technology of Patent Document 1, in order to keep each precious metal ratio in the first and second predetermined regions within a predetermined range, it is necessary to control the amount of the electrode base material and the precious metal alloy chip to be melted with high precision when laser welding the electrode base material and the precious metal alloy chip. Therefore, the technology of Patent Document 1 has difficulty in ensuring the joint reliability between the electrode base material and the precious metal chip alloy when the variation in the laser irradiation position is large. In other words, the technology of Patent Document 1 cannot ensure the joint reliability between the electrode base material and the precious metal chip alloy when the precious metal ratio in the first and second predetermined regions is wider than the range specified in Patent Document 1.

[0006] The present invention has been made in consideration of the above problems, and aims to provide a spark plug electrode that can ensure the bonding reliability between the Ni alloy base material and the precious metal tip alloy while widening the range of the precious metal ratio both on the boundary side between the molten resolidified portion and the precious metal alloy tip, and on the boundary side between the molten resolidified portion and the Ni alloy base material, as well as a spark plug using the same. [Means for solving the problem]

[0007] One aspect of the present invention is A spark plug electrode (1) having a center electrode (10) including a Ni alloy base material (101) and a precious metal alloy tip (102) welded to the Ni alloy base material, A molten resolidified portion (103) containing a component of the Ni alloy base material and a component of the precious metal alloy chip is formed between the Ni alloy base material and the precious metal alloy chip, The precious metal alloy tip is made of an Ir-Pt-Ta alloy containing Pt: 2% by mass or more and 23% by mass or less, and Ta: 0.3% by mass or more and 5.4% by mass or less, In a cross section of the center electrode taken along a central axis (C), The maximum width of the melted and resolidified portion in the direction of the central axis is H max year, A distance of 0.1×H from a first boundary (B1) between the melted and resolidified portion and the precious metal alloy tip in the direction of the central axis. max The minimum value of the precious metal ratio α1 on a first imaginary line (L1) drawn in parallel with the first boundary at a position entering the melted and resolidified portion side by α1 min year, A distance of 0.1×H from a second boundary (B2) between the molten and resolidified portion and the Ni alloy base material in the direction of the central axis. max The maximum value of the precious metal ratio α2 on a second imaginary line (L2) drawn parallel to the second boundary at a position entering the melted and resolidified portion side by α2 max year, α2 max / α1 min The maximum value of the precious metal ratio calculated by the formula is β max When β max ≦3.6, The average value of the precious metal ratio α1 on the first virtual line is α1 ave More than 25% The average value of the precious metal ratio α2 on the second virtual line is α2 ave is 90% or less, Located on the spark plug electrode (1).

[0008] Another aspect of the present invention is The spark plug (2) has the spark plug electrode. Effect of the Invention

[0009] The spark plug electrode has the above configuration. The spark plug has the above spark plug electrode. Therefore, according to the spark plug electrode and the spark plug, even if the range of the precious metal ratio is wider than before on both the first boundary side between the molten resolidified portion and the precious metal alloy tip and the second boundary side between the molten resolidified portion and the Ni alloy base material, it is possible to suppress the crack growth due to the thermal cycle.

[0010] Therefore, according to the above spark plug electrode and the above spark plug, the bonding reliability between the Ni alloy base material and the precious metal tip alloy can be ensured with a wider range of precious metal ratio than conventionally on both the boundary side between the molten resolidified portion and the precious metal alloy tip, and on the boundary side between the molten resolidified portion and the Ni alloy base material.

[0011] In addition, the symbols in parentheses described in the claims and the means for solving the problems indicate the correspondence with the specific means described in the embodiments described below, and do not limit the technical scope of the present invention. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a half cross-sectional view of a spark plug electrode and a spark plug according to a first embodiment. [Diagram 2] FIG. 2 is an enlarged perspective view of a portion of the spark plug electrode according to the first embodiment. [Diagram 3] FIG. 3(a) is a cross-sectional view showing an example of an electrode cross section taken along a central axis direction of a center electrode of a spark plug electrode according to embodiment 1, and FIG. 3(b) is an enlarged cross-sectional view showing a part of FIG. 3(a). [Figure 4] FIG. 4 is a cross-sectional view showing another example of an electrode cross section taken along the central axis direction of the center electrode of the spark plug electrode according to the first embodiment. [Diagram 5] FIG. 5 is a diagram for illustrating a method for measuring the strength of the melted and resolidified portion used for calculating the strength-stress ratio (SS ratio) in the spark plug electrode and the spark plug according to the second embodiment. [Figure 6] FIG. 6 is a diagram showing a 3D model for FEM analysis used for calculating, by FEM analysis, thermal stress used for calculating a strength-stress ratio (SS ratio) in the spark plug electrode and the spark plug according to the second embodiment. [Figure 7]Figure 7(a) is a graph showing the relationship between the precious metal ratio α1ave on the first imaginary line on the precious metal alloy chip side and the presence or absence of crack progression when a cooling-heating cycle test was conducted with 200 cooling-heating cycles for samples 1 to 5 of the experimental example and the comparative sample, and Figure 7(b) is a graph showing the relationship between the precious metal ratio α2ave on the second imaginary line on the precious metal alloy chip side and the presence or absence of crack progression when a cooling-heating cycle test was conducted with 200 cooling-heating cycles for samples 1 to 5 of the experimental example and the comparative sample. [Figure 8] FIG. 8(a) is a graph showing the relationship between the precious metal ratio α1ave on the first imaginary line on the precious metal alloy chip side and the presence or absence of crack progression when a thermal cycle test was conducted on sample 3 and sample 5 of the experimental example with 300 thermal cycles, and FIG. 8(b) is a graph showing the relationship between the precious metal ratio α2ave on the second imaginary line on the precious metal alloy chip side and the presence or absence of crack progression when a thermal cycle test was conducted on sample 3 and sample 5 of the experimental example with 300 thermal cycles. [Figure 9] FIG. 9 is a diagram showing the relationship between the maximum value βmax of the precious metal ratio and the crack length ratio when a thermal cycle test was carried out on Sample 3 of the experimental example with 200 thermal cycles. [Figure 10] FIG. 10 is a diagram showing the relationship between the maximum value βmax of the precious metal ratio and the crack length ratio when a thermal cycle test was carried out with 300 thermal cycles for Samples 3 and 5 of the experimental example. [Figure 11] FIG. 11 is a diagram showing the relationship between the Pt content (mass%) and Ta content (mass%) of the Ir-Pt-Ta alloy constituting the precious metal alloy tip, obtained in the experimental example, and the SSR, which is an index of the improvement rate of the joining reliability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A spark plug electrode and a spark plug according to an embodiment will be described below with reference to Fig. 1 to Fig. 6. Note that the following embodiment is an example embodied in a spark plug electrode and a spark plug used in an internal combustion engine such as an engine. The spark plug electrode and the spark plug according to the present disclosure are not limited to the following examples.

[0014] (Embodiment 1) A spark plug electrode 1 and a spark plug 2 of a first embodiment will be described with reference to Fig. 1 to Fig. 4. As illustrated in Fig. 1 and Fig. 2, the spark plug 2 of the present embodiment has a spark plug electrode 1 of the present embodiment. The spark plug electrode 1 of the present embodiment has a center electrode 10 including a Ni alloy base material 101 and a precious metal alloy tip 102 welded to the Ni alloy base material 101.

[0015] The spark plug 2 includes a cylindrical (tubular) housing 21 made of a metal material such as iron. A thread 21a is cut on the outer periphery of the lower part of the housing 21 (metal shell). The outer diameter of the thread 21a may be, for example, 10 mm.

[0016] The lower part of a cylindrical (tubular) insulator 22 is inserted inside the housing 21. The insulator 22 is made of an insulating material such as alumina. The housing 21 and the insulator 22 are joined together by crimping an upper end 21d of the housing 21.

[0017] The center electrode 10 is inserted and held inside the insulator 22. The center electrode 10 is formed in a cylindrical shape using a base material such as a Ni alloy having excellent heat resistance. Specifically, the inner material (center material) of the center electrode 10 is made of copper or the like, and the outer material (outer material) is made of a Ni alloy. That is, the center electrode 10 uses a Ni alloy base material 101 as an electrode base material. The tip portion of the center electrode 10 protrudes from the lower end (one end) of the insulator 22. As illustrated in FIG. 2, the center electrode 10 has a cylindrical (column-shaped) precious metal alloy tip 102 at its tip.

[0018] The center electrode 10, the housing 21, and the insulator 22 are arranged coaxially. That is, the central axes of the center electrode 10, the housing 21, and the insulator 22 coincide with the central axis C of the spark plug 2.

[0019] A central shaft portion 28 and a terminal portion 29 are electrically connected to the upper portion of the central electrode 10. An external circuit that applies a high voltage for generating sparks is connected to the terminal portion 29. A gasket 200 used for mounting the spark plug to an internal combustion engine is provided on the upper end portion of the screw 21a of the housing 21. When the spark plug 2 is mounted in the combustion chamber of the internal combustion engine, the central electrode 10 and the ground electrode 24 of the spark plug 2 are exposed to the combustion chamber. The direction from the central electrode 10 to the tip portion 24a of the ground electrode 24 corresponds to the center direction of the combustion chamber.

[0020] At a position facing the tip surface 102a of the precious metal alloy tip 102 (center electrode 10), a ground electrode 24 is disposed, which is curved and extends integrally from the lower end surface 21c (one end surface) of the housing 21. That is, the ground electrode 24 is connected to the housing 21 and curved so that the tip portion 24a faces the tip surface 102a of the precious metal alloy tip 102. The ground electrode 24 is formed of a Ni alloy or the like. A spark gap is formed between the tip surface 102a of the precious metal alloy tip 102 and the tip portion 24a of the ground electrode 24. That is, discharge is performed between the tip surface 102a of the precious metal alloy tip 102 and the tip portion 24a of the ground electrode 24, and a discharge spark is formed. The outer diameter of the precious metal alloy tip 102 can be, for example, 0.7 mm, and the length in the direction of the central axis C can be, for example, 0.6 mm before welding.

[0021] The precious metal alloy tip 102 is made of an Ir-Pt-Ta alloy. The Ir-Pt-Ta alloy constituting the precious metal alloy tip 102 is specifically an Ir alloy containing Pt: 2% by mass or more and 23% by mass or less, and Ta: 0.3% by mass or more and 5.4% by mass or less. More specifically, the Ir-Pt-Ta alloy constituting the precious metal alloy tip 102 can be an Ir alloy containing Pt: 2% by mass or more and 23% by mass or less, Ta: 0.3% by mass or more and 5.4% by mass or less, with the remainder being Ir and unavoidable impurities.

[0022] From the viewpoint of increasing the rate of improvement in the joint reliability between the Ni alloy base material 101 and the precious metal alloy tip 102, the above-mentioned Ir-Pt-Ta alloy can preferably be made to have Pt: 2.5 mass% or more and 19 mass% or less, and Ta: 0.75 mass% or more and 5.2 mass% or less, and more preferably Pt: 3 mass% or more and 15 mass% or less, and Ta: 1.2 mass% or more and 5 mass% or less.

[0023] As illustrated in FIG. 2, a molten resolidified portion 103 is formed between the Ni alloy base material 101 and the precious metal alloy tip 102. The molten resolidified portion 103 contains the components of the Ni alloy base material 101 (such as Ni) and the components of the precious metal alloy tip 102 (such as Ir, Pt, and Ta). The molten resolidified portion 103 is a portion that is resolidified after the Ni alloy base material 101 and the precious metal alloy tip 102 are melted and mixed, and is in a state in which the components of the Ni alloy base material 101 and the precious metal alloy tip 102 are mixed. Such a molten resolidified portion 103 can be formed, for example, by laser welding the precious metal alloy tip 102 to the tip of the Ni alloy base material 101.

[0024] 3(a) and 4 show an example of an electrode cross section along the central axis (C) of the central electrode. The melted resolidified portion 103 shown in FIG. 3(a) and FIG. 4 is formed by melting and resolidifying a part of the Ni alloy base material and a part of the Ir-Pt-Ta alloy constituting the precious metal tip alloy from the electrode outer peripheral surface 103a toward the central axis C. In the electrode cross section along the central axis C, the melted resolidified portion 103 may be continuous in the center as shown in FIG. 3(a), or may not be continuous in the center as shown in FIG. 4 (it may be discontinuous in the center). In other words, when the melted resolidified portion 103 is continuous in the center, there is no unmelted portion between the Ni alloy base material 101 and the precious metal alloy tip 102 where the Ni alloy base material 101 and the precious metal alloy tip 102 are not melted. On the other hand, when the melted resolidified portion 103 is not continuous in the center, there is an unmelted portion between the Ni alloy base material 101 and the precious metal alloy tip 102. In the unmelted portion, the components of the Ni alloy base material 101 and the components of the precious metal alloy tip 102 are not mixed.

[0025] Here, as illustrated in FIGS. 3 and 4, in the electrode cross section along the central axis C of the central electrode 10, the maximum width of the molten resolidified portion 103 in the direction of the central axis C is defined as H max In addition, a distance of 0.1×H from the first boundary B1 between the melted and resolidified portion 103 and the precious metal alloy tip 102 in the direction of the central axis C is defined as max The minimum value of the precious metal ratio α1 on the first imaginary line L1 drawn in parallel with the first boundary B1 at a position entering the melted and resolidified portion 103 side by α1 min The average value of the precious metal ratio α1 on the first virtual line L1 is defined as α1 ave Similarly, from the second boundary B2 between the melted and resolidified portion 103 and the Ni alloy base material 101 in the direction of the central axis C, max The maximum value of the precious metal ratio α2 on the second imaginary line L2 drawn in parallel with the second boundary B2 at a position entering the melted and resolidified portion 103 side by α2 max The average value of the precious metal ratio α2 on the second virtual line L2 is defined as α2ave Also, α1 min α2 max As a percentage of α2 max / α1 min The maximum value of the precious metal ratio calculated by the formula is β max It is defined as:

[0026] The first boundary B1 mentioned above is a boundary line where the interface between the molten resolidified portion 103 and the precious metal alloy tip 102 appears on the electrode cross section along the central axis C direction of the central electrode 10. Similarly, the second boundary B2 is a boundary line where the interface between the molten resolidified portion 103 and the Ni alloy base material 101 appears on the electrode cross section along the central axis C direction of the central electrode 10. As illustrated in FIG. 3, when the molten resolidified portion 103 formed by melting and resolidifying from the electrode outer peripheral surface 103a toward the central axis C is continuous at the center, the first virtual line L1 and the second virtual line L2 are continuous at the center of the molten resolidified portion 103. On the other hand, as illustrated in FIG. 4, when the molten resolidified portion 103 formed by melting and resolidifying from the electrode outer peripheral surface 103a toward the central axis C is discontinuous at the center, the first virtual line L1 and the second virtual line L2 are discontinuous at the center of the molten resolidified portion 103.

[0027] Furthermore, the precious metal ratio α1 on the first imaginary line L1 mentioned above can be specifically defined as α1(i) when the number of measurement points on the first imaginary line L1 is i=1, . . . , N (N is a natural number equal to or greater than 20). Here, α1(i) is the precious metal ratio at a position on the first imaginary line L1 corresponding to the number of measurement points i. Therefore, the minimum value α1 of the precious metal ratio α1 on the first imaginary line L1 is min Specifically, it can be said that the value of α1(i) is the smallest among the precious metal ratios α1(i) measured at positions corresponding to the number of measurement points i (i=1, . . . , N) on the first imaginary line L1. In addition, the average value α1 of the precious metal ratios α1 on the first imaginary line L1 aveSpecifically, it can be said that α1(i) is the arithmetic average value of each precious metal ratio α1(i) measured at a position corresponding to measurement point i (i = 1,...,N) on the first virtual line L1.

[0028] Similarly, the precious metal ratio α2 on the second imaginary line L2 can be specifically defined as α2(j) when the number of measurement points on the second imaginary line L2 is j=1, . . . , M (M is a natural number equal to or greater than 20). Here, α2(j) is the precious metal ratio at the position corresponding to the measurement point j on the second imaginary line L2. Therefore, the maximum value α2 of the precious metal ratio α2 on the second imaginary line L2 is max Specifically, it can be said that the value of α2(j) is the maximum value among the precious metal ratios α2(j) measured at positions corresponding to the number of measurement points j (j=1, . . . , M) on the second imaginary line L2. In addition, the average value α2 of the precious metal ratios α2 on the second imaginary line L2 ave Specifically, it can be said that α2(j) is the arithmetic average value of each precious metal ratio α2(j) measured at a position corresponding to the measurement point j (j = 1,...,M) on the second virtual line L2.

[0029] The above-mentioned precious metal ratio can be calculated as mass % of the precious metal element. In the spark plug electrode 1 of this embodiment, the electrode base material is a Ni alloy base material 101, and the precious metal alloy tip 102 contains Ir and Pt as precious metals. Therefore, the precious metal elements used to calculate the precious metal ratio in the spark plug electrode 1 of this embodiment are Ir and Pt. Therefore, the precious metal ratio at each measurement point can be calculated specifically by (Ir mass + Pt mass) / (total mass of all metal elements) × 100. The precious metal ratio at each measurement point can be measured by performing qualitative and quantitative analysis of elements on the first virtual line L1 and the second virtual line L2 using a fluorescent X-ray analyzer.

[0030] At the spark plug electrode 1, β max is β max ≦3.6, α1 aveis 25% or more, α2 ave The technical significance of these regulations is explained below.

[0031] The spark plug 2 is repeatedly heated and cooled during use. For example, the spark plug 2 used in an internal combustion engine such as an engine is exposed to a thermal cycle as the internal combustion engine is repeatedly started and stopped. In general, due to temperature changes caused by thermal cycles, thermal stress occurs at the bonding interface between the Ni alloy base material and the precious metal alloy tip, and cracks occur at the maximum stress point. Then, when the cracks grow due to the repeated thermal stress and the holding force of the precious metal alloy tip becomes equal to or less than the external stress, the precious metal alloy tip falls off.

[0032] On the other hand, in the spark plug electrode 2, a precious metal alloy tip 102 made of an Ir-Pt-Ta alloy having a specific composition containing Ir as a main material, 2 to 23 mass % of Pt, and 0.3 to 5.4 mass % of Ta, and a Ni alloy base material 101 are melted and resolidified to form a molten resolidified portion 103. Therefore, it is possible to realize high strength and low Young's modulus of the molten resolidified portion 103. By increasing the strength of the molten resolidified portion 103, it is possible to suppress the occurrence of cracks due to the thermal stress and the progress of cracks. In addition, since the thermal stress is expressed by the product of thermal strain and Young's modulus, by making the molten resolidified portion 103 have a low Young's modulus, it is possible to reduce the thermal stress generated by temperature changes during use.

[0033] In the melted and resolidified portion 103, which can achieve high strength and low Young's modulus, β max As long as the average value α1 of the precious metal ratio α1 on the first boundary B1 side between the melted and resolidified portion 103 and the precious metal alloy tip 102 is within the above specific range, ave 25% or more, the average value of the precious metal ratio α2 on the second virtual line α2 ave Even if the range is expanded to 90% or less, the bonding reliability between the Ni alloy base material 101 and the precious metal alloy tip 102 can be ensured.

[0034] The above-mentioned β max is significant as an index for measuring the bonding reliability between the Ni alloy base material 101 and the precious metal alloy tip 102. max is β max The smaller the value of β, the higher the joint reliability. max The larger the value of α1(i), the lower the bonding reliability. The larger the value of α1(i) described above, the smaller the thermal stress at the interface between the molten resolidified portion 103 and the precious metal alloy tip 102. On the other hand, the smaller the value of α2(j) described above, the smaller the thermal stress at the interface between the molten resolidified portion 103 and the Ni alloy base material 101. In other words, the smaller the precious metal ratio β=α2(j) / α1(i), the smaller the thermal stress in the entire molten resolidified portion 103, and the higher the bonding reliability between the Ni alloy base material 101 and the precious metal alloy tip 102. As described above, the minimum value of α1(i) is α1 min and the maximum value of α2(j) is α2 max Therefore, the maximum value of the precious metal ratio β is max is β max =α2 max / α1 min It can be calculated from the formula:

[0035] The above-mentioned precious metal ratio can be adjusted by adjusting the laser light output, irradiation position, irradiation angle, number of irradiations, irradiation time, irradiation area, etc. when laser welding the precious metal alloy chip 102 to the Ni alloy base material 101.

[0036] According to the spark plug electrode 1 and the spark plug 2 of this embodiment, even if the range of the precious metal ratio is wider than before on both the first boundary B1 side between the molten resolidified portion 103 and the precious metal alloy chip 102 and the second boundary B2 side between the molten resolidified portion 103 and the Ni alloy base material 101, it is possible to suppress the propagation of cracks due to thermal cycles.

[0037] Therefore, according to the spark plug electrode 1 and spark plug 2 of this embodiment, the joining reliability between the Ni alloy base material 101 and the precious metal alloy tip 102 can be ensured with a wider range of precious metal ratio than conventionally on both the boundary side between the molten resolidified portion 103 and the precious metal alloy tip 102 and the boundary side between the molten resolidified portion 103 and the Ni alloy base material 101.

[0038] In the spark plug electrode 1 and the spark plug 2 of the present embodiment, when the maximum temperature during use is in the range of 800° C. or more and 900° C. or less, the crack propagation caused by the thermal cycle can be suppressed, and the joint reliability between the Ni alloy base material 101 and the precious metal alloy tip 102 can be improved. From this viewpoint, α1 ave is preferably 30% or more, more preferably 35% or more, and even more preferably 40% or more, and α2 ave can be preferably 85% or less, and more preferably 80% or less.

[0039] In the spark plug electrode 1 and the spark plug 2 of the present embodiment, β max is preferably β max In the spark plug electrode 1 and the spark plug 2 of the present embodiment, from the viewpoint of suppressing the growth of cracks and further ensuring good joint reliability, for example, when the maximum temperature during use is set to 800° C., β max It is preferable that β satisfies ≦3.6. For example, when the maximum temperature during use is 850°C, max It is preferable that β satisfies ≦2.8. For example, when the maximum temperature during use is 900°C, max It is preferable that the above-mentioned β max , α1 ave , α2 ave The ranges can be combined in any manner.

[0040] In addition, the spark plug electrode 1 and the spark plug 2 of the present embodiment can reduce the amount of precious metal on the side of the precious metal alloy tip 102 to be melted during laser welding, and therefore the size of the precious metal alloy tip 102 can be reduced. Therefore, according to the spark plug electrode 1 and the spark plug 2 of the present embodiment, the manufacturing cost of the spark plug 2 can be reduced by miniaturizing the precious metal alloy tip 102. Furthermore, the spark plug electrode 1 and the spark plug 2 of the present embodiment can easily control the amount of the Ni alloy base material 101 and the precious metal alloy tip 102 to be melted during laser welding. Therefore, according to the spark plug electrode 1 and the spark plug 2 of the present embodiment, the manufacturing cost of the spark plug 2 can be reduced by improving the manufacturability of the spark plug electrode 1 in which the joint reliability between the Ni alloy base material 101 and the precious metal alloy tip 102 is ensured.

[0041] In the spark plug electrode 1 and the spark plug 2 of the present embodiment, the molten resolidified portion 103 is formed by melting and resolidifying from the outer circumferential surface 103 a of the electrode toward the central axis C. When the molten resolidified portion 103 is configured to be continuous at the center in a cross section of the electrode taken along the direction of the central axis C, the following effects are achieved.

[0042] That is, when the center electrode 10 is repeatedly heated and cooled during use of the spark plug 2, a large thermal stress is likely to occur in the unmelted portion where the components of the Ni alloy base material 101 and the precious metal alloy tip 102 are not mixed. Therefore, when the melted resolidified portion 103 is not continuous at the center and has an unmelted portion, cracks caused by repeated thermal stress due to thermal cycles are likely to develop from the unmelted portion. In contrast, when the melted resolidified portion 103 is continuous at the center, there is no unmelted portion, so that cracks are unlikely to develop from the center of the melted resolidified portion 103 due to repeated thermal stress due to thermal cycles. Therefore, this configuration makes it easier to improve the joint reliability between the Ni alloy base material 101 and the precious metal alloy tip 102.

[0043] (Embodiment 2) A spark plug electrode 1 and a spark plug 2 according to a second embodiment will be described with reference to Figures 5 and 6. Note that, among the reference characters used in the second and subsequent embodiments, the same reference characters as those used in the previous embodiments denote the same components, etc. as those in the previous embodiments, unless otherwise specified.

[0044] The spark plug electrode 1 of this embodiment satisfies 1.2≦SSR. The spark plug electrode 1 of this embodiment is provided. Hereinafter, the above-mentioned SSR will be mainly described.

[0045] In the spark plug electrode 1 of this embodiment, the SS ratio is a strength-stress ratio obtained by dividing the strength of the molten resolidified portion 103 at 800°C (hereinafter referred to as the strength of the molten resolidified portion) by the thermal stress generated in the molten resolidified portion 103 when a temperature difference of 780°C is applied. That is, the strength-stress ratio (SS ratio) can be calculated by the formula: (strength of the molten resolidified portion at 800°C) / (thermal stress generated in the molten resolidified portion 103 when a temperature difference of 780°C is applied). The larger the SS ratio, the higher the strength against stress, and therefore the higher the joining reliability.

[0046] The strength of the molten resolidified portion used in the calculation of the SS ratio is specifically the stress at which the molten resolidified portion 103 is bent in a high-temperature environment of 800 ° C., and can be measured by a bending deformation test shown in FIG. 5. That is, as shown in FIG. 5, a load is applied to the molten resolidified portion 103 using a pressing jig 90 from a direction perpendicular to the central axis C of the center electrode 10. The load [N] at which the molten resolidified portion 103 buckles is measured, and the stress generated in the molten resolidified portion 103 at that time is calculated to be the strength of the molten resolidified portion. The strength of the molten resolidified portion is the arithmetic average value of each measured value obtained with n number = 5.

[0047] On the other hand, the thermal stress used to calculate the SS ratio can be calculated by FEM analysis of the stress generated in the molten resolidified portion 103 due to a thermal load when a temperature difference ΔT=780° C. is applied using a 3D model for FEM analysis of the spark plug 2 (spark plug electrode 1) shown in FIG. 6. In this case, the Mises stress obtained from the analysis is used as the type of stress value. The 3D model for FEM analysis of the spark plug 2 is modeled based on the actual dimensions of the spark plug 2. For the molten resolidified portion 103, material properties that change depending on the composition of the Ni alloy base material 101 and the precious metal alloy tip 102 are used.

[0048] SS1 and SS2 are calculated according to the above-mentioned formula for calculating the SS ratio. SS1 is the SS ratio obtained for the comparative center electrode in which the Ir-Pt-Ta alloy constituting the precious metal alloy tip 102 is replaced with an Ir-Rh alloy containing 90% by mass of Ir and 10% by mass of Rh. SS2 is the SS ratio obtained for the above-mentioned center electrode 10 in which the precious metal alloy tip 102 is made of an Ir-Pt-Ta alloy containing 2% by mass or more and 23% by mass or less of Pt and 0.3% by mass or more and 5.4% by mass or less of Ta.

[0049] The SSR can be calculated as the ratio of SS2 to SS1 by the formula SS2 / SS1. The SSR is an index that is significant as the improvement ratio of the joint reliability of the center electrode 10 to that of a comparative center electrode having a precious metal alloy tip 102 made of an Ir:90 mass%-Rh:10 alloy. SS2 changes according to the composition ratio of Pt and Ta in the Ir-Pt-Ta alloy. Therefore, the SSR also changes accordingly. Details will be shown in the experimental examples.

[0050] When the spark plug electrode 1 and spark plug 2 of this embodiment satisfy 1.2≦SSR, the effect of improving the joint reliability between the Ni alloy base material 101 and the precious metal alloy tip 102 can be enhanced compared to a comparative spark plug electrode and spark plug having a comparative center electrode.

[0051] From the viewpoint of further improving the effect of improving the joint reliability between the Ni alloy base material 101 and the precious metal alloy tip 102, the SSR is preferably 1.3 or more, more preferably 1.4 or more, and further preferably 1.5 or more.

[0052] The other configurations and effects are the same as those of the first embodiment.

[0053] (Experimental Example) <Sample preparation> Each sample of the spark plug electrode described above was prepared by the following procedure.

[0054] That is, the front end surface of the Ni alloy base material and the rear end surface of the precious metal alloy tip made of an Ir-Pt-Ta alloy having a predetermined chemical composition were brought into contact with each other, and the region including the contact portion between the two was irradiated with a laser beam from the outer periphery side of the precious metal alloy tip toward the central axis of the precious metal alloy tip using a laser welding machine, thereby welding the precious metal alloy tip to the Ni alloy base material. The laser welding machine used was capable of irradiating a YAG laser beam. The oscillation method of the laser beam was pulse oscillation. As a result, a melted and resolidified portion containing the components of the Ni alloy base material and the components of the precious metal alloy tip was formed over the entire circumference between the Ni alloy base material and the precious metal alloy tip. As a result, spark plug electrodes of Samples 1 to 5 having different precious metal ratios were produced. In these samples, the precious metal alloy tip was made of an Ir-Pt-Ta alloy, so the precious metal elements used to calculate the precious metal ratio were Ir and Pt. The above-mentioned precious metal ratio was adjusted by adjusting the output, irradiation position, irradiation angle, number of irradiations, irradiation time, irradiation area, etc. of the laser light when laser welding the precious metal alloy chip to the Ni alloy base material.

[0055] The chemical compositions of the precious metal alloy chips used in the preparation of the above-mentioned Samples 1 to 5 are as follows: In the preparation of all samples, a Ni alloy containing Cr and Fe, with the balance being Ni and unavoidable impurities, was used as the Ni alloy base material. [Sample 1] Ir-Pt-Ta alloy containing 2% by mass of Pt, 5.4% by mass of Ta, and the remainder being Ir and unavoidable impurities. [Sample 2] Ir-Pt-Ta alloy containing 23% by mass of Pt, 5.4% by mass of Ta, and the remainder being Ir and unavoidable impurities. [Sample 3] Ir-Pt-Ta alloy containing 23 mass% Pt, 0.3 mass% Ta, and the remainder being Ir and unavoidable impurities. [Sample 4] Ir-Pt-Ta alloy containing 2% by mass of Pt, 0.3% by mass of Ta, and the remainder being Ir and unavoidable impurities. [Sample 5] Ir-Pt-Ta alloy containing 15% by mass of Pt, 1.2% by mass of Ta, and the remainder being Ir and unavoidable impurities.

[0056] In addition, a comparative sample spark plug electrode having a different precious metal ratio was obtained in the same manner as above, except that an Ir-Rh alloy (Ir: 90 mass %-Rh: 10 mass %) was used as the precious metal alloy constituting the precious metal alloy tip instead of the Ir-Pt-Ta alloy. In this comparative sample, since the precious metal alloy tip is made of an Ir-Rh alloy, the precious metal elements used to calculate the precious metal ratio are Ir and Rh.

[0057] <Cold-heat cycle test> For samples 1 to 5 and a comparison sample, which have different chemical compositions of the precious metal alloy constituting the precious metal alloy chip, the precious metal ratio α1 on the first virtual line ave and the precious metal ratio α2 on the second virtual line ave A thermal cycle test was carried out to verify the bonding reliability of the central electrode. The thermal cycle test was carried out by repeating the cycle of changing the temperature of the central electrode between the upper limit temperature (800°C, 850°C, or 900°C) and the lower limit temperature (room temperature 25°C) 200 or 300 times, and then checking whether or not cracks had progressed in the electrode cross section along the central axis of the central electrode. In this test, the precious metal ratio α1 on the first virtual line was ave Verification of the relationship between the crack propagation and the precious metal ratio α2 on the second virtual line aveThe relationship between the temperature and the occurrence of crack propagation was verified using separate samples. Figures 7 and 8 show the results of the above-mentioned thermal cycle test.

[0058] As shown in FIG. 7, the precious metal ratio α1 without crack propagation was obtained for a comparative sample of the prior art using a precious metal alloy tip made of an Ir-Rh alloy with Ir: 90 mass%-Rh: 10 mass%. ave , α2 ave The range of the precious metal ratio α1 without crack propagation obtained by the samples 1 to 5 using the precious metal alloy chips made of Ir-Pt-Ta alloy containing Pt: 2 mass% to 23 mass% and Ta: 0.3 mass% to 5.4 mass% ave , α2 ave It can be seen that the range of is wider in terms of the effective range for suppressing crack propagation due to thermal cycles.

[0059] In addition, as shown in FIG. 8, the precious metal ratio α1 at which cracks do not progress was obtained for sample 3 using a precious metal alloy tip made of an Ir-Pt-Ta alloy containing 23 mass % Pt and 0.3 mass % Ta. ave , α2 ave In comparison with the range of the above, the precious metal ratio α1 without crack propagation was obtained by using sample 5 using a precious metal alloy chip made of an Ir-Pt-Ta alloy containing 15 mass% Pt and 1.2 mass% Ta. ave , α2 ave It can be seen that the effective range for suppressing crack propagation due to thermal cycles is wider in the range of 1.5. It can also be seen that the thermal cycle life, which can suppress crack propagation due to thermal cycles, can be extended by 1.5 times in the case of sample 5.

[0060] <β max Survey on > In the thermal cycle test results shown in Figs. 7 and 8, the maximum value β maxThe relationship with the crack length ratio was obtained by investigating the relationship between the crack length and the crack length ratio. The crack length ratio indicates the ratio of the crack length to the total length when the crack is assumed to grow, and is the larger of the values ​​calculated for the first virtual line L1 and the second virtual line L2. Specifically, it was calculated from the following formula. The crack length ratio was calculated by measuring each value from the electrode cross section along the central axis direction of the central electrode in sample 3 and sample 5. Figures 9 and 10 show the maximum value β of the precious metal ratio. max The relationship between the crack length ratio and Crack length ratio=(crack length on the first imaginary line L1) / (total length of the first imaginary line L1) or (crack length on the second imaginary line L2) / (total length of the second imaginary line L2), whichever is larger

[0061] As shown in FIG. max β according to the maximum temperature at which the spark plug is used so as to satisfy ≦3.6 max By adjusting β, it is possible to suppress the crack propagation caused by the thermal cycle and to improve the joint reliability between the Ni alloy base material and the precious metal tip alloy. max By making the ratio β≦3.6, it is possible to suppress the crack propagation and ensure good joint reliability. Similarly, when the maximum temperature during use is 850°C, max ≦2.8, if the maximum temperature during use is 900℃, β max By making the ratio ≦2.0, it is possible to suppress the progress of cracks and ensure good joint reliability.

[0062] In addition, as shown in FIG. 10, when the number of thermal cycles in the thermal cycle test is increased to 300 cycles, in the case of sample 3, when the maximum temperature during use is 900°C, β max By making β≦1.0, it is possible to suppress the crack propagation and ensure good joint reliability. maxIt can be seen that by setting β to 1.0 or less, which is smaller than 2.0, it is possible to reliably suppress the crack propagation. On the other hand, in the case of sample 5, when the maximum temperature during use is 900°C, max By making the ratio β≦2.0, it is possible to suppress the crack propagation and ensure good joint reliability. max It can be seen that good joint reliability is obtained even when the value of is large. This is thought to be because the improvement rate of the joint reliability is higher in sample 5 than in sample 3. Therefore, as shown below, a more detailed investigation was conducted on the improvement rate of the joint reliability.

[0063] <Improvement rate of joint reliability> As described above, the improvement rate of the joint reliability can be evaluated by the index of SSR. Fig. 11 shows the relationship between the Pt content (mass%) and the Ta content (mass%) of the Ir-Pt-Ta alloy constituting the precious metal alloy tip and the SSR. In Fig. 11, the improvement rate of the joint reliability is considered to be average when SSR<1.2, the improvement rate of the joint reliability is considered to be good when 1.2≦SSR<1.5, where the effect of the present disclosure becomes clearer, and the improvement rate of the joint reliability is considered to be excellent when 1.5≦SSR, where the effect of the present disclosure becomes clearer.

[0064] 11, when the Pt content in the Ir-Pt-Ta alloy is 2% by mass or more and 23% by mass or less and the Ta content is 0.3% by mass or more and 5.4% by mass or less, 1.2≦SSR<1.5 is satisfied, and it is understood that the improvement rate of the joint reliability can be made good. Also, when the Pt content in the Ir-Pt-Ta alloy is 2% by mass or more and 23% by mass or less and the Ta content is 0.3% by mass or more and 5.4% by mass or less, 1.5≦SSR is satisfied, and it is understood that the improvement rate of the joint reliability can be made good.

[0065] The present invention is not limited to the above-described embodiment and experimental examples, and various modifications are possible without departing from the spirit and scope of the present invention. Furthermore, the configurations shown in the above-described embodiment and experimental examples can be arbitrarily combined with each other.

[0066] The features of the present invention are as follows. [1] A spark plug electrode (1) having a center electrode (10) including a Ni alloy base material (101) and a precious metal alloy tip (102) welded to the Ni alloy base material, A molten resolidified portion (103) containing a component of the Ni alloy base material and a component of the precious metal alloy chip is formed between the Ni alloy base material and the precious metal alloy chip, The precious metal alloy tip is made of an Ir-Pt-Ta alloy containing Pt: 2% by mass or more and 23% by mass or less, and Ta: 0.3% by mass or more and 5.4% by mass or less, In a cross section of the center electrode taken along a central axis (C), The maximum width of the melted and resolidified portion in the direction of the central axis is H max year, A distance of 0.1×H from a first boundary (B1) between the melted and resolidified portion and the precious metal alloy tip in the direction of the central axis. max The minimum value of the precious metal ratio α1 on a first imaginary line (L1) drawn in parallel with the first boundary at a position entering the melted and resolidified portion side by α1 min year, A distance of 0.1×H from a second boundary (B2) between the molten and resolidified portion and the Ni alloy base material in the direction of the central axis. max The maximum value of the precious metal ratio α2 on a second imaginary line (L2) drawn parallel to the second boundary at a position entering the melted and resolidified portion side by α2 max year, α2 max / α1 min The maximum value of the precious metal ratio calculated by the formula is β max When β max ≦3.6, The average value of the precious metal ratio α1 on the first virtual line is α1ave More than 25% The average value of the precious metal ratio α2 on the second virtual line is α2 ave is 90% or less, Spark plug electrode(1). [2] The melted and resolidified portion is formed by melting and resolidifying from the outer peripheral surface (103a) of the electrode toward the central axis, In a cross section of the electrode taken along the central axis direction, The melted and resolidified portion is continuous at the center. [1] A spark plug electrode according to the present invention. [3] The strength-stress ratio, which is the value obtained by dividing the strength of the molten and resolidified portion at 800°C by the thermal stress generated in the molten and resolidified portion when a temperature difference of 780°C is applied, is defined as the SS ratio; The SS ratio of a comparative center electrode formed by replacing the Ir-Pt-Ta alloy constituting the precious metal alloy tip with an Ir-Rh alloy having a mass percentage of Ir of 90% and Rh of 10% is defined as SS1; The SS ratio of the center electrode in which the precious metal alloy tip is made of the Ir-Pt-Ta alloy is SS2, When the improvement rate of the joint reliability calculated by the formula SS2 / SS1 as the ratio of the SS2 to the SS1 is defined as SSR, 1.2≦SSR; A spark plug electrode according to [1] or [2]. [4] A spark plug (2) having the spark plug electrode according to any one of [1] to [3]. [Explanation of symbols]

[0067] 1 Spark plug electrode 10 Center electrode 101 Ni alloy base material 102 Precious metal alloy chips 103 Melted and resolidified area C Central axis of the center electrode B1: First boundary between the melted and resolidified part and the precious metal alloy tip B2 Second boundary between the melted and resolidified area and the Ni alloy base material L1 First virtual line L2 Second virtual line 2 Spark plugs

Claims

1. A spark plug electrode (1) having a center electrode (10) including a Ni alloy base material (101) and a precious metal alloy tip (102) welded to the Ni alloy base material, A molten resolidified portion (103) containing a component of the Ni alloy base material and a component of the precious metal alloy chip is formed between the Ni alloy base material and the precious metal alloy chip, The noble metal alloy tip is made of an Ir-Pt-Ta alloy containing Pt: 2% by mass or more and 23% by mass or less, and Ta: 0.3% by mass or more and 5.4% by mass or less, In a cross section of the center electrode taken along a central axis (C), The maximum width of the melted and resolidified portion in the direction of the central axis is H max year, A distance of 0.1×H from a first boundary (B1) between the molten and resolidified portion and the precious metal alloy tip in the direction of the central axis. max The minimum value of the precious metal ratio α1 on a first imaginary line (L1) drawn in parallel with the first boundary at a position entering the melted and resolidified portion side by α1 min year, A distance of 0.1×H from a second boundary (B2) between the molten and resolidified portion and the Ni alloy base material in the direction of the central axis. max The maximum value of the precious metal ratio α2 on a second imaginary line (L2) drawn in parallel with the second boundary at a position entering the melted and resolidified portion side by α2 max year, α2 max / α1 min The maximum value of the precious metal ratio calculated by the formula is β max When β max ≦3.6、 The average value of the precious metal ratio α1 on the first virtual line is α1 ave More than 25% The average value of the precious metal ratio α2 on the second virtual line is α2 ave is 90% or less, Spark plug electrode (1).

2. The melted and resolidified portion is formed by melting and resolidifying from the outer peripheral surface (103a) of the electrode toward the central axis, In a cross section of the electrode taken along the central axis direction, The melted and resolidified portion is continuous at the center.

2. The spark plug electrode of claim 1.

3. The strength-stress ratio, which is the value obtained by dividing the strength of the molten resolidified portion at 800 ° C. by the thermal stress generated in the molten resolidified portion when a temperature difference of 780 ° C. is applied, is defined as the SS ratio; The SS ratio of a comparative center electrode formed by replacing the Ir-Pt-Ta alloy constituting the precious metal alloy tip with an Ir-Rh alloy having a mass percentage of Ir: 90% and Rh: 10% is defined as SS1; The SS ratio of the center electrode in which the precious metal alloy tip is made of the Ir-Pt-Ta alloy is SS2, When the improvement rate of the joint reliability calculated by the formula SS2 / SS1 as the ratio of the SS2 to the SS1 is defined as SSR, 1.2≦SSR; 3. A spark plug electrode according to claim 1 or 2.

4. A spark plug (2) comprising a spark plug electrode according to claim 1 or 2.

Citation Information

Patent Citations

  • Spark plug electrode, manufacturing method thereof, and spark plug

    JP2017536665A

  • Spark plug, and center electrode manufacturing method

    JP2021082539A

  • Ignition plug

    JP2023028769A